-25+6x-46+2x=

Simple and best practice solution for -25+6x-46+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25+6x-46+2x= equation:


Simplifying
-25 + 6x + -46 + 2x = 0

Reorder the terms:
-25 + -46 + 6x + 2x = 0

Combine like terms: -25 + -46 = -71
-71 + 6x + 2x = 0

Combine like terms: 6x + 2x = 8x
-71 + 8x = 0

Solving
-71 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '71' to each side of the equation.
-71 + 71 + 8x = 0 + 71

Combine like terms: -71 + 71 = 0
0 + 8x = 0 + 71
8x = 0 + 71

Combine like terms: 0 + 71 = 71
8x = 71

Divide each side by '8'.
x = 8.875

Simplifying
x = 8.875

See similar equations:

| -z^2-4z+7=0 | | -46+2x+5x+48= | | 0.45t^2-2t+1=0 | | 5(x-3)+7=3x+2(-3+x) | | -s+6+3s=8s | | -20+z=4 | | 7b=11+95+41 | | -32-6x+8x-14= | | 1.126=2x+3 | | 2p+1=3p+7 | | -14x-39+5x+48= | | f(x)=3x^2+7x+1 | | -8y+7-5y=-18 | | 8x-14+5x+48= | | k^2+12k-14=0 | | -1/9n=17 | | 3(2+x)=4-(x+2) | | 7x+27=4x+12 | | -28=4h-3h | | X+(-7y)+(-4x)+8y= | | -20=4(8z-2) | | 2x+6y-8+19x=0 | | (2x-7)2=81 | | 5.5=0.5x-8.3/2.2 | | -3(4r-2)=-30 | | -18(x+1)+6(4x-5)=5(x-4)+8 | | 4X+y=8z | | 4/5x-2=18 | | 110=2x+4y | | 9(6x+4)= | | (5w-3)-(w-1)= | | y=x^3+3x^2-72x+5 |

Equations solver categories